(untitled) (Research, Society and Development, 2021)
The Covid-19 pandemic as a health and humanitarian crisis has alerted society to its short- and long-term consequences. Therefore, the present study presents and discusses the data obtained from the application of a didactic sequence regarding Covid-19 and its environmental impacts. This study is of a descriptive nature, with a qualitative and interpretative approach with analysis based on the discourse of the collective subject. Developed with students from the discipline of Principles of Ethnobiology and Environmental Education of a degree course in Biological Sciences, this sequence consisted of two word-clouds, followed by conversation circles for critical-reflective discussion, a questionnaire and finally, the elaboration drawings on the perceptions regarding this pedagogical path. The word-clouds and discussion circles brought topics linked to mental health, such as fear and anxiety, in addition to having aligned the environmental issue, such as garbage and pollution. Most students pointed to the socio-emotional issue as one of the biggest impacts of the pandemic, including being cited as the dimension of sustainability that was most impacted in the current context. Therefore, the subject as an integral part of the environment, can, through the recognition of care and environmental impacts, advance in environmental educational practices that promote increasingly sustainable development.